Study Literatur Use Of Active-Assistive Range Of Motion Cylindrical Grip And Spherical Grip Towards Increasing Upper Extremity Muscle Strength In Stroke Patients (Studi Literatur Penggunaan ROM Aktif-Asistif Cylindrical Grip dan Spherical Grip Terhadap Peningkatan Kekuatan Otot Ekstremitas Atas Pada Pasien Stroke) - Cahyani, Gita; MN, Shobirun; Purnomo, Sajan Eko Chambari (Journal of Applied Health Management and Technology, 2022)
ABSTRACTStroke is damage to brain tissue due to disruption of blood flow to the brain. One of the effects that occur in stroke patients is weakness on one side of the body, such as the upper extremity. Exercises to stimulate movement in the hands can be in the form of active-assistive ROM cylindrical grip and spherical grip. The purpose of this research is to identify research articles that describe the use of ROM cylindrical grip and spherical grip to increase upper extremity muscle strength in stroke patients. Design this research is a literature review study. Article searches were carried out comprehensively through a database of national and international indexed research journals with the inclusion and exclusion criteria. The types of research articles are quasi experiment, pre-experimental study, and retrospective study. The research articles obtained were 11 articles, analyzed and synthesized in a tabular format. The results of the literature review is active-assisted ROM cylindrical grip and spherical grip are used as limb movement exercises in the rehabilitation process for stroke patients, namely cylindrical grip ROM, spherical grip both using simple tools (tissue rolls, baseball) as well as technological innovations that have developed such as Robot-assisted Therapy, 3D immersive virtual reality, and Hand Extension Robot Orthosis (HERO) Grip Glove. The conclusion of this study is ROM cylindrical grip and spherical grip are used as post-stroke rehabilitation exercises that are useful for training muscle strength, especially when gripping, preventing joint stiffness, as well as in carrying out daily activities.Â ABSTRAKStroke adalah kerusakan jaringan otak akibat terganggunya alirah darah menuju otak. Salah satu dampak yang terjadi pada pasien stroke adalah kelemahan di salah satu sisi tubuh, seperti ekstremitas atas. Latihan untuk menstimulasi gerak pada tangan dapat berupa latihan ROM aktif-asistif cylindrical grip dan spherical grip. Penelitian ini bertujuan untuk mengidentifikasi artikel-artikel penelitian yang memaparkan penggunaan latihan ROM aktif-asistif cylindrical grip dan spherical grip terhadap peningkatan kekuatan otot ekstremitas atas pada pasin stroke.Jenis penelitian kajian literatur. Pencarian artikel dilakukan secara komprehensif melalui database jurnal penelitian terindeks nasional dan internasional yang memenuhi kriteria inklusi dan eklusi. Jenis artikel penelitian yang digunakan sebagai referensi adalah quasi experiment, pre-experimental study, dan retrospective study. Artikel penelitian yang didapatkan sebanyak 11 artikel, dianalisis dan disintesis dalam format tabel. Hasil kajian literatur menunjukkan ROM aktif-asistif cylindrical grip dan spherical grip dimanfaatkan sebagai latihan gerak ekstremitas dalam proses rehabilitasi pada pasien stroke yaitu ROM cylindrical grip, spherical grip baik yang menggunakan alat sederhana (tissue gulung, bola kasti) maupun inovasi teknologi yang sudah berkembang seperti Robot-assisted Therapy, 3D immersive virtual realility, dan Hand Extension Robot Orthosis (HERO) Grip Glove. Penggunaan ROM aktif-asistif cylindrical grip dan spherical grip sebagai latihan rehabilitasi pasca stroke dimana bermanfaat untuk melatih kekuatan otot, terutama ketika mengenggam, mencegah kekakuan sendi, serta dalam melakukan aktivitas sehari-hari.